Assessment of Utility of Mobile Based Agro-advisory Services in NCR Delhi - Kumbhare, N.V.; Sharma, Nishi; Ahmad, Nafees; Joshi, Pratibha; Dabas, J.P.S. (Indian Journal of Extension Education, 2019)
The study on assessment of mobile based agro-advisory services was conducted in four selected villages i.e. Kutbi (Muzaffarnagar, Uttar Pradesh), Khajurka (Palwal, Haryana) Rajpur (Aligarh, Uttar Pradesh) and Beenjpur (Alwar, Rajasthan) during 2017. The weather based agro-advisory messages were provided to the selected farmers. Thirty (30) registered farmers from each village were selected who were sent regular mobile advisory messages from IARI. Hence, a total of 120 respondents from the selected four villages constituted the sample of the study. The result revealed that more than 90 per cent of the respondent opined that they read the agro advisory messages received from IARI, language of the messages were easily understandable, clear and readable and messages received were included local and familiar words for easy understanding. Also 80 per cent of the respondents expressed that information received through messages were adaptable in local field conditions and a majority (88 %) of the respondents expressed that the length of content of messages were adequate.The study has revealed that the informationgathered through agro-advisory service has been found veryuseful and helpful to the farmers and they havestarted gaining interest in accessing information and decision making on thecrops management by utilizing agro advisory services.
Keywords: Mobile based agro-advisory; Opinion; Need; Preferences